ETIKA JUAL BELI DALAM ISLAM - Syaifullah, Syaifullah (State Institute of Islamic Studies (IAIN) Palu, 2014)
Buying and selling is a means of mankind to meet the needs of each individual.On the one hand, the seller can be a buyer, and on the other hand, the buyer may be a seller,till he or sheÂ meetsÂ the latest buyer who acts as a consumer. Thus, buying and sellingÂ can be very susceptible to manipulation to something desired by one party in order to gain benefit even beyond rational matter. Therefore, buying and selling in Islam cannot be separated from ethics. The ethics must be held by all parties in order to maintain public interest for all people. The purpose to eastablish a safe, peaceful, and honest market system in order to avoid wrong-doing system that can be detrimental to all partiesKata Kunci: Etika, Jual-Beli, ijÄb-qabÅ«l